Determination of S(Iv) Oxoanions at Poly[Ru(5-No 2-Phen) 2cl Tetrapyridylporphyrin Glassy Carbon Modified Electrode - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Aguirre-Quintana, M; Aguirre-Quintana, M; Mendoza-Espinola, L; Mendoza-Espinola, L (2012)
Glassy carbon electrodes modified with conducting polymers of Ni(II), Zn(II) and metal free tetraruthenated porphyrin were evaluated for reduction and oxidation processes of S(IV) oxoanions in Na 2SO 3/water-ethanol at pH1.0 and 3.5, showing electrocatalytic activity. A Ni(II) film was able to reduce the S(IV) oxoanions selectively in presence of high concentration of gallic acid. The Ni(II) film was also used as an amperometric sensor toward S(IV) oxoanions reduction in white wine samples showing a detection and quantification limit of 1.40mgL -1 and 4.68mgL -1, respectively. These results are promising for the electrochemical determination of S(IV) using conducting polymers from these macrocycles. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.